STRATEGI BERTAHAN HIDUP IBU TUNGGAL DALAM PEMENUHAN KEBUTUHAN KELUARGA (Studi Kasus di Desa Jajag Kabupaten Banyuwangi) - Sinta Dewi, Engky Dona (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This thesis is entitled "Survival Strategies of Single Mothers in Meeting Family Needs (Case Study in Jajag Village, Gambiran District, Banyuwangi Regency). Single mothers, who are generally widows with children, face heavier economic and social burdens than intact families. This is because many women who after marriage choose not to work or are prohibited from working by their husbands so that they are completely dependent on their husband's income. The purpose of this study is to analyze the survival strategies of single parent families in Jajag Village, Banyuwangi. Which in writing uses qualitative research with a case study approach where a process of collecting data and information carefully in a program, event, activity, process or group of individuals. The formulation of the problem in this study is What are the survival strategies of single parent families in Jajag Village, Banyuwangi? By using the theory of actor action proposed by Max Weber consisting of 4 actions, namely Instrumental Rationality, Instrumental Rationality, Value Rationality and Value Rationality. The results of the analysis show that single mothers in meeting family needs by working at a minimum due to the limitations of their education. Single mothers choose to work from home because they have to carry out dual roles as parents. Older adults. These jobs include fried food sellers, vegetable sellers, laundry workers, farm laborers, and meatball vendors. Based on the research findings, it can be concluded that the survival strategies of single-parent families in Jajag Village, Banyuwangi, are implemented through various economic and social activities to meet family needs. In productive activities, single mothers fulfill dual roles as breadwinners and child caretakers. These strategies include working from home by selling food and vegetables, or running a grocery store, working as laborers such as farm laborers and laundry workers, and implementing dual incomes by having more than one job or involving adult children to support the family economy.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: single mother; family; survive